2003
DOI: 10.1016/s0168-583x(02)01947-x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of intense laser pulses with atomic clusters: Measurements of ion emission, simulations and applications

Abstract: This review paper provides a general introduction to the interaction of intense (>10 15 W cm À2 ), femtosecond laser pulses with atomic clusters in the size range 500-10 5 atoms. A nanoplasma model of the laser-cluster interaction is used to elucidate the underlying physics. Measurements of ion emission from the laser-cluster interaction are presented together with numerical simulations. Emerging applications are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 77 publications
0
4
0
1
Order By: Relevance
“…Under such conditions ions may achieve up to MeV kinetic energy. This line of research was pioneered experimentally by Ditmire (1998) and collaborators (Ditmire et al 1997, Tisch et al 2003 who even demonstrated the possibility to initiate nuclear fusion reactions with fast D + ions in molecular clusters (Ditmire et al 1999). The underlying physical mechanisms have been explained by several theoretical models, e.g.…”
Section: Femtochemistry Optimal Control and Strong Laser Fieldsmentioning
confidence: 99%
“…Under such conditions ions may achieve up to MeV kinetic energy. This line of research was pioneered experimentally by Ditmire (1998) and collaborators (Ditmire et al 1997, Tisch et al 2003 who even demonstrated the possibility to initiate nuclear fusion reactions with fast D + ions in molecular clusters (Ditmire et al 1999). The underlying physical mechanisms have been explained by several theoretical models, e.g.…”
Section: Femtochemistry Optimal Control and Strong Laser Fieldsmentioning
confidence: 99%
“…Understanding these interactions is crucial for future experiments involving the imaging of biological molecules, protein nanocrystals, DNA, or viruses. van der Waals clusters in the gas phase represent an ideal test bed for investigating the fragmentation physics of molecular systems in intense x-rays because no energy can be exchanged with a surrounding medium, and the interaction of high-intensity, near-infrared light with these atomic systems is widely understood [1,2]. The interaction of high-intensity extreme UV pulses with Xe clusters has been investigated in recent years at a photon energy of 90 eV and intensities up to 6 Â 10 14 W=cm 2 at the freeelectron laser in Hamburg (FLASH) and have been reported in a series of publications [3][4][5][6][7][8].…”
mentioning
confidence: 99%
“…The direct optical ionization begins when laser pulse liberates a small number of electrons. Field ionization is described in this model by Ammosov et al [18,22,24], and collisional ionization, which occurs from inelastic collisions between electrons and ions, is described by the Lotz formula [9,18,23]. Due to the high excitation and hot electrons and densities reached inside the cluster, collisional ionization is the dominant ionization mechanism in the nanoplasma leading to the production of highly charged ions.…”
Section: Ionization Mechanismsmentioning
confidence: 99%
“…Instead, the ions gain energy in the hydrodynamic expansion, where the thermal energy of the electrons is converted to ion kinetic energy or through coulomb explosion. For a hydrodynamic expansion, the mean ion energy will be of order [24]…”
Section: Cluster Expansionmentioning
confidence: 99%